A Multiplex Crystal Digital PCR for Detection of African Swine Fever Virus, Classical Swine Fever Virus, and Porcine Reproductive and Respiratory Syndrome Virus - Shi, Kaichuang; Chen, Yating; Yin, Yanwen; Long, Feng; Feng, Shuping; Liu, Huixin; Qu, Sujie; Si, Hongbin (Frontiers in Veterinary Science, 2022)
African swine fever (ASF), classical swine fever (CSF), and porcine reproductive and respiratory syndrome (PRRS) are highly infectious diseases of domestic pigs and wild boars. Co-infections of ASF virus (ASFV), CSF virus (CSFV), and PRRS virus (PRRSV) have been reported in different pig farms. Early differential detection and diagnosis of ASFV, CSFV, and PRRSV in the clinical samples is very important for effective prevention and control of these diseases. A multiplex crystal digital PCR (dPCR) was developed for differential detection of ASFV, CSFV, and PRRSV in this study, targeting p72, 5' untranslated region (UTR) and ORF7 genes, respectively. The different reaction conditions were optimized, and the specificity, sensitivity and repeatability of the assay were evaluated. The results showed that the multiplex crystal dPCR was able to accurately and differentially detect ASFV, CSFV, and PRRSV with a limit of detection of 4.69×10-1 copies/μL, respectively for ASFV, CSFV, and PRRSV, and could not detect other porcine viruses, i.e. foot-and-mouth disease virus (FMDV), Senecavirus A (SVA), atypical porcine pestivirus (APPV), pseudorabies virus (PRV), porcine circovirus type 2 (PCV2), porcine parvovirus (PPV). The assay showed excellent repeatability and reproducibility, with coefficients of variation (CV) of the intra- and inter-assay from 0.09% to 1.40%, and from 0.64% to 2.26%, respectively. The 289 clinical samples from different pig herds in Guangxi province, China were tested by the multiplex crystal dPCR and a reference multiplex real-time quantative RT-PCR (qRT-PCR) established previously in our laboratory, the positive rates of ASFV, CSFV, and PRRSV were 30.10%, 13.49% and 22.49% by the multiplex crystal dPCR, and 24.57%, 8.65% and 18.34% by the multiplex qRT-PCR, with coincidence rates of 94.66%, 95.16% and 95.84%, respectively. The results indicated that the established multiplex crystal dPCR was a specific, sensitive and accurate method for detection and quantification of ASFV, CSFV, and PRRSV. This is the first report on the multiplex dPCR for detecting ASFV, CSFV, and PRRSV.